Feasibility Study Rencana Infrastruktur STIE Ekuitas - Kurniawan, Gatot Iwan; Dagustani, Dani; Nurfitriana, Annisa; Firmansyah, Yayan (STIE Ekuitas, 2019)
STIE Ekuitas as one of developed college has reached to the stage that requires it to build or add infrastructure. Some of the reasons that underlie the situation is inadequate capacity of existing facilities including insufficient parking space and space limitation to develop or create a lab, discussion room, and simulation room. In order to develop the infrastructure, it requires a good planning so that the purpose of the research is to make a simulation of space requirements based on the estimated capability data from STIE Ekuitas, then prepare an infrastructure and facilities development plan and finally make a feasibility study on investment in infrastructure and facilities development plans. The method used will refer to the standard method in infrastructure development and will be analyzed in detail using quantitative descriptive methods. Keywords: Infrastructure; Feasibility Study; Invesment.